2016
DOI: 10.1021/acsami.6b03451
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Network Structure in Poly(vinylidene fluoride)/Carbon Nanotube Nanocomposites Using Carbon Black: Toward Improvements of Conductivity and Piezoresistive Sensitivity

Abstract: Piezoresistive poly(vinylidene fluoride) (PVDF) nanocomposites are very intriguing for strain sensor applications in structural health monitoring (SHM) systems. In general, high piezoresistive sensitivity combined with broad measurable strain ranges are greatly favored in those sensors. Here, a facile strategy, i.e. constructing strain susceptible conductive networks using hybrid filler systems consisting of carbon nanotubes (CNTs, 0.5-1 wt %) and carbon black (CB, 0.5-4 wt %), was introduced to tune both elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
121
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(122 citation statements)
references
References 48 publications
1
121
0
Order By: Relevance
“…Probably, carbon nanotubes (CNTs) are among the most studied reinforcements due to their intrinsic characteristics including high aspect ratio, outstanding electrical and mechanical properties, and versatility for surface functionalization. The CNT/PVDF composites enable new applications in different sectors, including membranes for ultrafiltration [3], superhydrophobic surfaces [4] fuel cell electrodes, charge transport layers in sensor systems [5], high energy storage systems [6,7], infrared detectors [8], electromagnetic interference shielding and radar absorbing coatings for military energy systems [9], electrodes for electrocardiograms [10], actuators and pressure sensors [11,12], in-vitro muscle cell growth [13], and structural health monitoring systems [14]. A comprehensive description of the applications of CNT-based PVDF composites can be found in several reviews [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Probably, carbon nanotubes (CNTs) are among the most studied reinforcements due to their intrinsic characteristics including high aspect ratio, outstanding electrical and mechanical properties, and versatility for surface functionalization. The CNT/PVDF composites enable new applications in different sectors, including membranes for ultrafiltration [3], superhydrophobic surfaces [4] fuel cell electrodes, charge transport layers in sensor systems [5], high energy storage systems [6,7], infrared detectors [8], electromagnetic interference shielding and radar absorbing coatings for military energy systems [9], electrodes for electrocardiograms [10], actuators and pressure sensors [11,12], in-vitro muscle cell growth [13], and structural health monitoring systems [14]. A comprehensive description of the applications of CNT-based PVDF composites can be found in several reviews [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In the beginning of this paper, we reviewed the vital importance of fillers in terms of the mechanical and electrical properties of PVDF matrix composites. The study of Ke et al [21] showed that, when the filler content of CB in the PVDF/CB system was 1.81 wt.%, the volume resistivity approached 10 13 , and, when the filler was increased to 4 wt.%, the volume resistivity decreased to about 10 3 . Huang et al [22] found that, with the increase in CB load, the electrical conductivity of composites increased obviously.…”
Section: Effect Of Notch Geometry On Stress-strain Relationship Of Simentioning
confidence: 99%
“…The dosage and proportion of hybrid conductive fillers are important to the tensile strain response of strain sensors [19,21]. The relation curves of CNTs/FLG dosage changes on the responsive sensitivity and tensile strain of SCGFs under 50% min −1 tensile rate are shown in Fig.…”
Section: Effect Of Cnts and Flg Loading On The Strain Sensing Behaviormentioning
confidence: 99%
“…In addition, the deterioration of mechanical properties for strain sensors could be dramatically avoided due to low percolation threshold caused by the synergistic effect of hybrid conductive fillers. Ke et al [21] manufactured a sensor based on PVDF/CB/CNTs composite, in which the higher the CB amount used, the higher the response sensitivity of sensors and the lower electroosmotic flow threshold. In this scenario, Liu et al [22] fabricated flexible strain sensors based on PU/CNTs/FLG conductive composites.…”
Section: Introductionmentioning
confidence: 99%